2015
DOI: 10.1001/jama.2015.16840
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Opioids vs NSAIDs and Larger vs Smaller Chest Tube Size on Pain Control and Pleurodesis Efficacy Among Patients With Malignant Pleural Effusion

Abstract: isrctn.org Identifier: ISRCTN33288337.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
154
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 19 publications
3
154
1
5
Order By: Relevance
“…Talc is the most commonly used pleurodesis agent and a meta-analysis supports its use as the sclerosant of choice [4,75]. Even within the context of large randomised trials, pleurodesis success rates remain under 80% and are almost certainly lower in everyday practice [9,10,76,77]. It has been proven that graded preparations (as opposed to small particle talc) should be used to minimise systemic talc particle dissemination and the risk of acute respiratory distress syndrome [78,79].…”
Section: Pleurodesismentioning
confidence: 99%
See 3 more Smart Citations
“…Talc is the most commonly used pleurodesis agent and a meta-analysis supports its use as the sclerosant of choice [4,75]. Even within the context of large randomised trials, pleurodesis success rates remain under 80% and are almost certainly lower in everyday practice [9,10,76,77]. It has been proven that graded preparations (as opposed to small particle talc) should be used to minimise systemic talc particle dissemination and the risk of acute respiratory distress syndrome [78,79].…”
Section: Pleurodesismentioning
confidence: 99%
“…Even today, no consensus exists about the optimal size of the chest drain and the time of removal of the tube post-pleurodesis. National guidelines advocate the use of small bore (<14 F) chest drains, but this is now challenged by the results of the largest study to specifically address tube size for MPE in terms of pleurodesis success [10]. Specifically, the TIME1 study showed that smaller chest tubes might be inferior to larger ones in terms of pleurodesis success [10].…”
Section: Pleurodesismentioning
confidence: 99%
See 2 more Smart Citations
“…The management of malignant pleural effusions has seen considerable progress within the past decade, with a number of randomised controlled trials now informing practice [1][2][3]. This progress, by contrast, has not been mirrored in non-malignant pleural disease, which has an evidence base still formed largely of observational studies.…”
Section: Introductionmentioning
confidence: 99%